Ceramic electronic component and preparation method and application thereof

By using barium titanate and Ba(Ti1-xSnx)O3 materials in a multi-layer chip ceramic capacitor, the dielectric material layer with Sn-rich and Sn-poor regions is designed, and the capacity reduction and TCC characteristics of MLCC in high temperature environments are solved. The problem is that high dielectric constant and excellent high and low temperature stability are achieved.

CN119446785APending Publication Date: 2025-02-14CHAOZHOU THREE CIRCLE GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411530785.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing multi-layer chip ceramic capacitors (MLCCs) have a lower capacity in high temperature environments, and the temperature coefficient (TCC) characteristics of the dielectric constant are poor, making it difficult to meet the usage requirements.

Method used

Barium titanate and Ba(Ti1-xSnx)O3 are used as raw materials for the preparation of the dielectric material layer. By designing the dielectric material layer into the first area rich in Sn and the second area leaning in Sn, a unique stress distribution is formed, which enhances the Dielectric constant and maintain high temperature TCC characteristics.

Benefits of technology

It realizes high dielectric constant, excellent high and low temperature stability and long service life of ceramic electronic components, meeting the performance requirements of X5R MLCC products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110423960000061
    Figure BDA0005110423960000061
  • Figure BDA0005110423960000071
    Figure BDA0005110423960000071
  • Figure BDA0005110423960000091
    Figure BDA0005110423960000091
Patent Text Reader

Abstract

The invention belongs to the field of electronic products, and particularly discloses a ceramic electronic component and a preparation method and application thereof.The ceramic electronic component comprises a dielectric material layer, the dielectric material layer is prepared from barium titanate and Ba (Ti1-xSnx) O3, and x is larger than or equal to 0.05 and smaller than or equal to 0.12; the dielectric material layer comprises a first region and a second region; the second area is distributed in the first area; the amount of substance of Sn in the first region is greater than the amount of substance of Sn in the second region; the amount of substance of Sn in the first area is 4-12% of the total amount of substance of Sn and Ti; the area of the first region is 10-35% of the total area of the dielectric material layer; the area of the second region is 65-90% of the total area of the dielectric material layer. The ceramic electronic component provided by the invention has a relatively high dielectric constant, relatively excellent high and low temperature stability and relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electronic products, and in particular relates to a ceramic electronic component and a preparation method and application thereof. Background Art

[0002] Generally, a ceramic electronic component using ceramic materials, such as a capacitor, an inductor, a piezoelectric element, a varistor or a thermistor, includes a ceramic body formed of the ceramic material, an internal electrode formed in the ceramic body, and an external electrode mounted on a surface of the ceramic body to be connected to the internal electrode.

[0003] Multilayer ceramic capacitors (MLCCs) are ceramic electronic components that are chip capacitors mounted on printed circuit boards of various electronic products such as image devices, such as liquid crystal displays (LCDs), plasma display panels (PDPs), computers, smartphones, mobile phones, etc., for charging or discharging in or from them.

[0004] In recent years, MLCC has been developing towards miniaturization and high capacity, and the requirements for dielectric constant of dielectric materials are getting higher and higher; MLCC needs to work in a wide range of temperature environments and maintain a relatively stable capacity, which also puts forward high requirements for the temperature coefficient (TCC) of dielectric constant of dielectric materials. Perovskite structural ceramics based on BaTiO3 are widely used in high-capacity MLCCs due to their excellent dielectric properties. In order to further improve the dielectric constant of BaTiO3, it is usually modified by ion substitution, such as using Zr / Hf / Sn to replace the B position (i.e., Ti position) in solid solution, so that its Curie temperature moves to room temperature, thereby obtaining a higher dielectric constant; although this method improves the room temperature dielectric constant, it cannot avoid the rapid decrease of the dielectric constant at the high temperature end. Therefore, the capacity of MLCC will drop rapidly in a high temperature environment, and the TCC characteristics are very poor, which is difficult to meet the use requirements. In ordinary single-phase BaTiO3 structural ceramic materials, high dielectric constant and stable TCC characteristics are usually difficult to coexist, and these problems seriously restrict the application of MLCC products. Summary of the invention

[0005] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a ceramic electronic component.

[0006] A second object of the present invention is to provide a method for preparing a ceramic electronic component.

[0007] A third object of the present invention is to provide application of the above ceramic electronic component in electronic products.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] The first aspect of the present invention provides a ceramic electronic component, comprising a dielectric material layer, wherein the raw materials for preparing the dielectric material layer include barium titanate and Ba(Ti 1-x Sn x )O3, 0.05≤x≤0.12;

[0010] The dielectric material layer includes a first region and a second region; the second region is distributed in the first region;

[0011] The amount of the Sn substance in the first region is greater than the amount of the Sn substance in the second region;

[0012] In the first region, the amount of Sn is 4-12% of the total amount of Sn and Ti;

[0013] The area of ​​the first region is 10 to 35% of the total area of ​​the dielectric material layer;

[0014] The area of ​​the second region is 65-90% of the total area of ​​the dielectric material layer.

[0015] There are Sn-rich regions (first regions) and Sn-poor regions (second regions) in the dielectric material layer of the present invention, forming a unique stress distribution. The Sn-rich region (first region) has a large lattice constant, which applies tensile stress to the lattice of the surrounding Sn-poor region (second region), thereby enhancing its ferroelectric displacement and improving the dielectric constant; the Sn-poor region (second region) maintains a normal ferroelectric phase and maintains high-temperature TCC characteristics.

[0016] In the present invention, Ba(Ti 1-x Sn x )O3, 0.05≤x≤0.12, for example, the value of x can be selected from 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095, 0.100, 0.105, 0.11, 0.115, 0.12 or a range consisting of any two of the above values.

[0017] In the first region of the present invention, the amount of Sn is 4-12% of the total amount of Sn and Ti, for example, it can be selected from 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% or a range consisting of any two of the above values. When the content of Sn in the first region is less than 4%, the lattice distortion of the first region is limited, it is difficult to apply sufficient tensile stress to the second region, and the dielectric constant is not significantly improved; when the content of Sn in the first region is higher than 12%, Sn is easy to diffuse into the second region, destroying the target structure and deteriorating the TCC performance at the high temperature end.

[0018] In the present invention, the area of ​​the first region is 10-35% of the total area of ​​the dielectric material layer, for example, it can be selected from 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or the range consisting of any two of the above values.

[0019] In the present invention, the area of ​​the second region is 65-90% of the total area of ​​the dielectric material layer, for example, it can be selected from 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or the range formed by any two of the above values. When the area of ​​the second region accounts for less than 65% of the total area of ​​the dielectric material layer, the ferroelectric phase content in the dielectric material layer is insufficient, and the TCC characteristics at the high temperature end are deteriorated; when the area of ​​the second region accounts for more than 90% of the total area of ​​the dielectric material layer, the stress structure action area is insufficient, and the dielectric constant improvement effect is not significant; at the same time, the second regions are easy to contact each other, resulting in a significant decrease in high temperature reliability.

[0020] Preferably, in the second region, the amount of Sn is 0-0.5% of the total amount of Sn and Ti, for example, it can be selected from 0%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5% or a range consisting of any two of the above values. When the content of Sn in the second region is higher than 0.5%, the Curie temperature moves significantly toward the low temperature direction, and the TCC performance at the high temperature end deteriorates.

[0021] Preferably, the ratio of the amount of Sn in the first region to the amount of Sn in the second region is ≥ 8, for example, the ratio of the amount of Sn in the first region to the amount of Sn in the second region can be selected from 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 or a range consisting of any two of the above values. When the ratio of the amount of Sn in the first region to the amount of Sn in the second region is less than 8, there is no unique stress distribution formed by the Sn-rich region (first region) and the Sn-poor region (second region) in the dielectric material layer, and it is difficult to improve the dielectric constant of the ceramic electronic component.

[0022] Preferably, barium titanate and Ba(Ti 1-x Sn x )O3 is 100%, the mass percentage of the barium titanate is 57-85%; the Ba(Ti 1-x Sn x )O3 has a mass percentage of 15 to 43%. The mass percentage of the barium titanate can be selected from 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85% or a range consisting of any two of the above values. The Ba(TiO3) has a mass percentage of 15 to 43%. The mass percentage of the barium titanate can be selected from 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85% or a range consisting of any two of the above values. 1-x Sn x The mass percentage of Ba(TiO3) may be selected from 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43% or the range consisting of any two of the above values. 1-x Sn x )O3 mass percentage is too low, the lattice distortion is small and the dielectric constant is not improved enough; Ba(Ti 1-x Sn x )When the mass percentage of O3 is too high, the content of Sn-rich region is too high, the Curie temperature is reduced, and the TCC characteristics are deteriorated, which cannot meet the performance requirements of X5R type MLCC products.

[0023] Preferably, the raw materials for preparing the dielectric material layer also include auxiliary components; the auxiliary components contain compounds of at least one element selected from rare earth elements, Mg, Mn, V, Ni, Fe, Cr, Cu, Si, Al, and B; further preferably, the auxiliary components are selected from at least one of Dy2O3, MgO, MnCO3, and SiO2.

[0024] Preferably, based on the total mass percentage of the dielectric material layer being 100%, the barium titanate and Ba(Ti 1- x Sn x)O3's total mass percentage is 93-95%, for example, can be selected from 93%, 93.1%, 93.2%, 93.3%, 93.4%, 93.5%, 93.6%, 93.7%, 93.8%, 93.9%, 94%, 94.1%, 94.2%, 94.3%, 94.4%, 94.5%, 94.6%, 94.7%, 94.8%, 94.9%, 95%; the mass percentage of the auxiliary components is 5-7%, for example, can be selected from 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7%.

[0025] Preferably, the ceramic electronic component is selected from a multilayer ceramic capacitor, an inductor, a piezoelectric element, a varistor or a thermistor; further preferably, the ceramic electronic component is a multilayer ceramic capacitor.

[0026] Preferably, the ceramic electronic component comprises a laminate and an external electrode; the laminate comprises dielectric material layers and internal electrode layers alternately laminated; an external electrode is respectively provided at both ends of the laminate, and the external electrode is electrically connected to the internal electrode layer.

[0027] Preferably, the ceramic electronic component further comprises a metal coating, and the metal coating is located on the surface of the outer electrode.

[0028] The second aspect of the present invention provides a method for preparing the ceramic electronic component according to the first aspect of the present invention, comprising the following steps:

[0029] S1: will include barium titanate, Ba(Ti 1-x Sn x ) The raw materials for preparing O3 are ground, mixed and then heat treated to obtain dielectric porcelain powder;

[0030] S2: preparing a ceramic slurry from raw materials including the dielectric ceramic powder;

[0031] S3: forming the ceramic slurry into a film, and then preparing a chip green body;

[0032] S4: debinding and sintering the chip green body to obtain a sintered body;

[0033] S5: preparing the sintered body into the ceramic electronic component.

[0034] The Ba(Ti) 1-x Sn x )O3 powder is the main component of the first region, barium titanate is the main component of the second region, and the Sn element contained in the second region is diffused from the first region. In the preparation of the present invention, barium titanate and Ba(Ti 1-x Sn x)O3 powder is mixed to make dielectric porcelain powder, and then made into ceramic slurry, and then made into ceramic electronic components. The formation reason of the dielectric material layer of the special structure of the present invention is: Ba(Ti 1-x Sn x ) The sintering temperature of O3 powder is relatively low. During sintering, it will first become porcelain, thus forming the first region. At this time, BaTiO3 is still in liquid state, and it will not sinter until the temperature is raised. Barium titanate material constitutes the main material of the second region, thus forming a dielectric material layer containing the first region and the second region.

[0035] The Ba(Ti) 1-x Sn x )O3 powder can be prepared by any method selected from the solid phase method, hydrothermal method, and coprecipitation method. Taking the solid phase method as an example, Ba(Ti 1-x Sn x )O3 powder preparation method comprises the following steps: ball milling and mixing the formulated amount of BaCO3, TiO2, SnO2, drying, calcining at 1050-1150°C for 2-4h in air atmosphere, and then crushing by high-energy ball milling to obtain.

[0036] Preferably, the step S1 is: comprising barium titanate, Ba(Ti 1-x Sn x )O3. Preparation of auxiliary components: The raw materials are ground and mixed and then heat-treated to obtain dielectric porcelain powder.

[0037] Preferably, the Ba(Ti 1-x Sn x )The particle size of O3 powder is 30~50nm.

[0038] Preferably, the heat treatment temperature is 300-400°C, for example, can be selected from 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or a range consisting of any two of the above values.

[0039] Preferably, the heat treatment time is 1 to 5 hours, for example, can be selected from 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or a range consisting of any two of the above values.

[0040] Preferably, the heat treatment atmosphere is an air atmosphere.

[0041] Preferably, the ceramic slurry comprises the following components in percentage by mass: 30-60% of dielectric ceramic powder, 30-60% of solvent, 2-8% of dispersant, and 5-10% of binder.

[0042] Preferably, the solvent is selected from at least one of toluene, ethanol and isobutanol.

[0043] Preferably, the dispersant is selected from at least one of triethyl phosphate, castor oil and triolein.

[0044] Preferably, the binder is selected from at least one of polyvinyl butyral and polyvinyl alcohol.

[0045] Preferably, the step S2 is: mixing raw materials including dielectric ceramic powder, solvent, dispersant and binder to obtain the ceramic slurry.

[0046] Preferably, the step S3 is: tape-casting the ceramic slurry to obtain a ceramic film, and then preparing an internal electrode layer on the ceramic film by screen printing or roller printing, laminating, hydrostatically pressing, and cutting to obtain a chip green body.

[0047] Preferably, the debinding temperature is 250-400°C, for example, it can be selected from 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or a range consisting of any two of the above values. The purpose of debinding is to remove organic matter in the chip green body.

[0048] Preferably, the debinding atmosphere is an air atmosphere.

[0049] Preferably, the sintering temperature is 1100-1300°C, for example, can be selected from 1100°C, 1110°C, 1120°C, 1130°C, 1140°C, 1150°C, 1160°C, 1170°C, 1180°C, 1190°C, 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C or a range consisting of any two of the above values.

[0050] Preferably, the sintering time is 1 to 2 hours.

[0051] Preferably, the sintering atmosphere is a mixture of hydrogen and nitrogen with a hydrogen content of 1-2%.

[0052] Preferably, the step S5 is: coating conductive copper paste on both ends of the sintered body, and then sintering at 700-900°C in a reducing atmosphere to form external electrodes at both ends of the sintered body to obtain the ceramic electronic component; further preferably, the step S5 is: coating conductive copper paste on both ends of the sintered body, and then sintering at 700-900°C in a reducing atmosphere to form external electrodes at both ends of the sintered body, and forming a metal plating layer on the surface of the external electrode to obtain the ceramic electronic component.

[0053] The third aspect of the present invention provides use of the ceramic electronic component described in the first aspect of the present invention in an electronic product.

[0054] The beneficial effects of the present invention are: compared with directly homogenously dissolving Sn in the dielectric material layer, the ceramic electronic component of the present invention forms a unique stress distribution between the first region and the second region by designing the structure of the dielectric material layer into a Sn-rich first region and a Sn-poor second region, specifically: the Sn-rich first region has a large lattice constant, exerts tensile stress on the surrounding Sn-poor second region lattice, thereby enhancing its ferroelectric displacement and improving the dielectric constant; the Sn-poor second region maintains a normal ferroelectric phase and maintains high-temperature TCC characteristics. Therefore, the ceramic electronic component of the present invention has a higher dielectric constant, better high and low temperature stability, and a longer service life. When the ceramic electronic component of the present invention is an MLCC product, its dielectric constant is not less than 3000, TCC is within ±15%, and the failure time of the accelerated life test is not less than 240min. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 Schematic diagram of the structure of a multilayer ceramic capacitor in an embodiment of the present invention.

[0056] Figure 2 FIG. 4 is a cross-sectional schematic diagram of a multilayer ceramic capacitor according to an embodiment of the present invention.

[0057] Figure 3 Schematic diagram of the structure of the dielectric material layer in an embodiment of the present invention. DETAILED DESCRIPTION

[0058] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0059] The raw material information used in Examples 1 to 10 and Comparative Examples 1 to 6 of the present invention is as follows:

[0060] BaTiO3 powder, commercially available, with a particle size range of 120 to 500 nm;

[0061] Ba(Ti 1-x Sn x )O3 powder preparation: According to Ba(Ti 1-x Sn x)O3, calculate the amount of BaCO3, TiO2 and SnO2, then weigh BaCO3, TiO2 and SnO2 (for example, when x=0.085, weigh the following raw materials in mass percentage: 69.67wt% BaCO3, 25.81wt% TiO2 and 4.52wt% SnO2), mix and disperse by ball milling (ball milling speed is 86rpm, ball milling time is 12h), dry at 150℃ for 4h, and calcine at 1150℃ in air atmosphere for 3h to obtain BTSn solid solution powder; then the BTSn solid solution powder is crushed to an average particle size (D 50 ) is 50nm, and Ba(Ti 1-x Sn x )O3 powder.

[0062] Dielectric porcelain powder: The dielectric porcelain powder is composed of a main component and a secondary component. Taking the total mass percentage of the dielectric porcelain powder as 100%, the secondary component is composed of the following components in mass percentage: 4.474wt% Dy2O3, 0.322wt% MgO, 0.919wt% MnCO3, 0.240wt% SiO2; the main component is BaTiO3 powder and Ba(Ti 1-x Sn x )O3 powder composition. The formula of the main components is shown in Table 1 below.

[0063] Table 1 Formula of main ingredients in Examples 1 to 10 and Comparative Examples 1 to 6

[0064]

[0065]

[0066] The preparation method of the dielectric porcelain powder in Examples 1 to 10 and Comparative Examples 1 to 6 of the present invention is as follows:

[0067] According to the formula, the main components and auxiliary components are weighed, mixed and dispersed by ball milling, the ball milling speed is 86 rpm, the ball milling time is 12 h, dried at 150 ° C for 4 h, and then heat treated at 300 ° C in air atmosphere for 2 h and crushed to obtain the required medium porcelain powder.

[0068] Example 1

[0069] This example provides a multilayer chip ceramic capacitor, including a laminate, a first external electrode and a second external electrode, wherein:

[0070] like Figure 1 As shown, the stacked body has a first main surface and a second main surface arranged opposite to each other in the thickness direction, a first side surface and a second side surface arranged opposite to each other in the width direction, and a first end surface and a second end surface arranged opposite to each other in the length direction.

[0071] like Figure 2 As shown, the stack includes dielectric material layers and internal electrode layers that are alternately stacked, the internal electrode layers include first internal electrodes and second internal electrodes, the first internal electrodes and the second internal electrodes are alternately arranged, a dielectric material layer is arranged between the first internal electrodes and the second internal electrodes, the first internal electrodes and the second internal electrodes are exposed to the first end surface and the second end surface respectively; the first main surface and the second main surface of the stack are both dielectric material layers to prevent the first internal electrode and the second internal electrode from being exposed.

[0072] The first external electrode and the second external electrode are respectively arranged on the first end surface and the second end surface of the stack, the first external electrode is electrically connected to the first internal electrode, and the second external electrode is electrically connected to the second internal electrode; the first external electrode and the second external electrode are provided with a metal coating on their surfaces. The material of the metal coating is selected from zinc, tin, or a combination of the two.

[0073] like Figure 3 As shown, the dielectric material layer includes a first region ( Figure 3 The black part in the figure) and the second area ( Figure 3 The white part in the figure), the second region is distributed in the first region, and in the first region, the amount of Sn substance is 8% of the total amount of Sn and Ti substance, that is, the tin content in the first region is 8%; in the second region, the amount of Sn substance is 0.34% of the total amount of Sn and Ti substance, that is, the tin content in the second region is 0.34%; the area of ​​the first region is 35% of the total area of ​​the dielectric material layer, and the area of ​​the second region is 65% of the total area of ​​the dielectric material layer. The specific parameters of the dielectric material layer are shown in Table 2 below.

[0074] The multilayer ceramic capacitor in this example is manufactured by a manufacturing method comprising the following steps:

[0075] S1: Preparation of Ba(Ti 1-x Sn x )O3 powder, and then prepare dielectric porcelain powder;

[0076] S2: Slurry preparation:

[0077] The composition of the slurry is 40wt% medium porcelain powder, 50wt% solvent, 2wt% dispersant, and 8wt% binder; the slurry is evenly dispersed in an organic liquid phase system according to the above ratio to prepare the required slurry; the solvent is a mixed solution of toluene and anhydrous ethanol in a mass ratio of 1:1; the dispersant is triethyl phosphate; and the binder is polyvinyl butyral.

[0078] S3: Green preparation:

[0079] The slurry obtained above is prepared into a ceramic film by tape casting or the like, and then an electrode is prepared on the surface of the film by screen printing, roller printing or the like, and then a chip green body is prepared by lamination, hydrostatic pressure and cutting;

[0080] S4: Debinding and sintering:

[0081] The chip green body obtained in S3 was heat treated in air atmosphere at 300°C for 26h to remove organic matter contained in the chip green body, and then sintered at 1100°C for 1.5h in a strong reducing atmosphere (a mixture of H2 and N2 with a hydrogen content of 2%) to obtain a chip sintered body;

[0082] S5: External electrode preparation:

[0083] Conductive copper paste is coated on both ends of the chip sintered body, and it is densified by sintering at 800°C in a weak reducing atmosphere; finally, a metal coating such as Ni and Sn is plated outside the copper electrode at its end to prepare a complete multilayer ceramic capacitor.

[0084] Embodiments 2 to 10

[0085] The multilayer ceramic capacitors in Examples 2 to 10 differ from Example 1 only in that at least one of the four parameters of the first region Sn content, first region area, second region Sn content, and second region area of ​​the dielectric material layer is different, as shown in Table 2 below.

[0086] The only difference between the preparation methods of the multilayer chip ceramic capacitors in Examples 2 to 10 and Example 1 is that the formula of the main component in the dielectric ceramic powder is different, as shown in Table 1.

[0087] Comparative Examples 1 to 4

[0088] The multilayer ceramic capacitors in Comparative Examples 1 to 4 differ from Example 1 only in that at least one of the four parameters of the first region Sn content, first region area, second region Sn content, and second region area of ​​the dielectric material layer is different, as shown in Table 2 below.

[0089] The preparation methods of the multilayer chip ceramic capacitors in Comparative Examples 1 to 4 are different from those in Example 1 only in that the formula of the main component in the dielectric ceramic powder is different, as shown in Table 1.

[0090] Comparative Example 5

[0091] The multilayer ceramic capacitor in this example is different from that in the first embodiment only in that the dielectric material layer in this example only contains the first region, and the Sn content in the first region is 8.5%.

[0092] The preparation method of the multilayer ceramic capacitor in this example is different from that in Example 1 only in that the main component of the dielectric ceramic powder in this example contains only Ba(Ti 1-x Sn x )O3, x is 0.085.

[0093] Comparative Example 6

[0094] The multilayer ceramic capacitor in this example is different from that in the first embodiment only in that the dielectric material layer in this example only contains the second region, and the Sn content in the second region is zero.

[0095] The only difference between the method for preparing the multilayer chip ceramic capacitor in this example and that in Example 1 is that the main component of the dielectric ceramic powder in this example only contains BaTiO3.

[0096] Table 2 Structural parameters of dielectric material layers in Examples 1 to 10 and Comparative Examples 1 to 6

[0097]

[0098] The values ​​of the Sn content in the first region, the Sn content in the second region, the area of ​​the first region, and the area of ​​the second region in Table 2 are all tested by TEM+EDS. Under TEM observation, the EDS energy spectrum scanning mode is used to analyze the content of each element in the region; when Sn / (Sn+Ti)≥2%, it is determined to be the first region, and Sn / (Sn+Ti)<2% is determined to be the second region, thereby obtaining the values ​​of the Sn content in the first region, the Sn content in the second region, the area of ​​the first region, and the area of ​​the second region.

[0099] Performance Testing:

[0100] The performance of the multilayer ceramic capacitors in Examples 1 to 10 and Comparative Examples 1 to 6 were tested according to the test methods and test conditions described in Table 3 below. The specific test results are shown in Table 4 below.

[0101] Table 3 Test methods and test conditions

[0102]

[0103] Table 4 Performance of multilayer ceramic capacitors

[0104]

[0105]

[0106] It can be seen from Table 4 that the multilayer ceramic capacitors in Examples 1 to 10 of the present invention adjust the four parameters of the Sn content in the first region, the Sn content in the second region, the area of ​​the first region and the area of ​​the second region in the dielectric material layer, so that the MLCC products have a higher dielectric constant, better high and low temperature stability, and extend their service life, specifically: the dielectric constant is not less than 3000, the TCC is within ±15%, and the failure time of the accelerated life test is not less than 240min.

[0107] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A ceramic electronic component, characterized in that: The dielectric material layer includes a dielectric material layer, wherein the dielectric material layer is prepared by raw materials including barium titanate and Ba(Ti 1-x Sn x )O3, 0.05≤x≤0.12; The dielectric material layer includes a first region and a second region; the second region is distributed in the first region; The amount of the Sn substance in the first region is greater than the amount of the Sn substance in the second region; In the first region, the amount of Sn is 4-12% of the total amount of Sn and Ti; The area of ​​the first region is 10 to 35% of the total area of ​​the dielectric material layer; The area of ​​the second region is 65-90% of the total area of ​​the dielectric material layer.

2. The ceramic electronic component according to claim 1, characterized in that: In the second region, the amount of Sn is 0 to 0.5% of the total amount of Sn and Ti.

3. The ceramic electronic component according to claim 1, characterized in that: The ratio of the amount of Sn in the first region to the amount of Sn in the second region is ≥8.

4. The ceramic electronic component according to claim 1, characterized in that: Barium titanate and Ba(Ti 1-x Sn x )O3 is 100%, the mass percentage of the barium titanate is 57-85%; the Ba(Ti 1-x Sn x )The mass percentage of O3 is 15~43%.

5. The ceramic electronic component according to claim 1, characterized in that: The raw materials for preparing the dielectric material layer also include auxiliary components; the auxiliary components contain compounds of at least one element selected from rare earth elements, Mg, Mn, V, Ni, Fe, Cr, Cu, Si, Al, and B.

6. The ceramic electronic component according to claim 5, characterized in that: Taking the total mass percentage of the dielectric material layer as 100%, the barium titanate and Ba(Ti 1-x Sn x )The total mass percentage of O3 is 93-95%, and the mass percentage of the auxiliary components is 5-7%.

7. The ceramic electronic component according to any one of claims 1 to 6, characterized in that: The ceramic electronic component is selected from a multilayer chip ceramic capacitor, an inductor, a piezoelectric element, a varistor or a thermistor.

8. The method for preparing a ceramic electronic component according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: will include barium titanate, Ba(Ti 1-x Sn x ) The raw materials for preparing O3 are ground, mixed and then heat treated to obtain dielectric porcelain powder; S2: preparing a ceramic slurry from raw materials including the dielectric ceramic powder; S3: forming the ceramic slurry into a film, and then preparing a chip green body; S4: debinding and sintering the chip green body to obtain a sintered body; S5: preparing the sintered body into the ceramic electronic component.

9. The method for preparing a ceramic electronic component according to claim 8, characterized in that: The heat treatment temperature is 300-400°C; And / or, the heat treatment time is 1 to 5 hours; And / or, the debinding temperature is 250-400°C; And / or, the sintering temperature is 1100-1300°C; And / or, the sintering time is 1 to 2 hours; And / or, the sintering atmosphere is a mixture of hydrogen and nitrogen with a hydrogen content of 1-2%.

10. Use of the ceramic electronic component according to any one of claims 1 to 7 in electronic products.

Citation Information

Cited By

  • Chip multilayer ceramic capacitor and preparation method thereof

    CN121662605A